Is time travel possible? - Hunter, Nick (Hunter, Nick. Top secret!, 2016)
"Do you think time travel will ever be possible? Will all the books and films that show time travel become a reality? How does the science work? In this...book, a mysterious figure called the Mystery Master sets you the challenge of investigating all the scientific theories surrounding time travel and encourages you to analyze the information that you have gathered. Once you have read the information in this book, you can figure out for yourselves: Is time travel possible?"--Amazon.com.